SYSTEM AND METHOD FOR SKIN DETECTION OF A HUMAN SUBJECT - VERKRUIJSSE WILLEM; DE HAAN GERARD (2018)
The present invention relates to a system and method of skin detection of a human subject using a textile product. The textile product (10, 31, 43) is made from or comprising textile including near-infrared, NIR, absorbing pigments. It supports and/or partially covers the human subject while skin detection and/or detection/monitoring vital signs of the human subject is carried out. A increased contrast between the textile product and skin in the NIR wavelength range is thus achieved. 本发明涉及种织物产品以及其用于支撑和/或部分覆盖人类对象的使用。织物产品(10、31、43)由含有吸收近红外NIR的颜料的织物制成或包括含有吸收近红外NIR的颜料的织物。它在执行皮肤探测和/或探测/监测人类对象的生命体征时支持和/或部分覆盖人类对象。因此实现了织物产品与NIR波长范围内的皮肤之间的对比度增加。